The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s11356-014-3930-4
|View full text |Cite
|
Sign up to set email alerts
|

Green algal over cyanobacterial dominance promoted with nitrogen and phosphorus additions in a mesocosm study at Lake Taihu, China

Abstract: Enrichment of waterways with nitrogen (N) and phosphorus (P) has accelerated eutrophication and promoted cyanobacterial blooms worldwide. An understanding of whether cyanobacteria maintain their dominance under accelerated eutrophication will help predict trends and provide rational control measures. A mesocosm experiment was conducted under natural light and temperature conditions in Lake Taihu, China. It revealed that only N added to lake water promoted growth of colonial and filamentous cyanobacteria (Micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 42 publications
3
24
0
Order By: Relevance
“…Inorganic nitrogen was another key factor for phytoplankton development. Previous studies suggest that moderate levels (0.3-0.8 mg L -1 ) of inorganic nitrogen are required for the growth and reproduction of Microcystis spp (Ma et al, 2015). In this study NH 3 -N was positively associated with Microcystis growth throughout the water column.…”
Section: Nutrients Impacts On Phytoplankton Biomasssupporting
confidence: 50%
See 2 more Smart Citations
“…Inorganic nitrogen was another key factor for phytoplankton development. Previous studies suggest that moderate levels (0.3-0.8 mg L -1 ) of inorganic nitrogen are required for the growth and reproduction of Microcystis spp (Ma et al, 2015). In this study NH 3 -N was positively associated with Microcystis growth throughout the water column.…”
Section: Nutrients Impacts On Phytoplankton Biomasssupporting
confidence: 50%
“…In this study water temperatures up to 28°C were important for Microcystis spp growth. Other studies have also shown that water temperature had an impact on cHABs (Ma et al, 2015). Nalewajko and Murphy (2001) noted that harmful cyanobacteria tolerate higher temperatures relative to other algae, while Okino (1973) commented that in several Japanese lakes Microcystis spp did not appear (germinate and develop) until the water temperature was >20°C.…”
Section: Water Temperature Light and Phmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, on a short time scale, this method is not appropriate for the control of algal blooms with long durations and large spatial scales in northern bays (Duan et al, ; Qin et al, ). Previous studies have investigated the effects of increasing nutrients (Chen, Fan, Teubner, & Dokulil, ; Ma et al, ; Paerl et al, ; Xu et al, ), physical factors such as water temperature, wind waves, and light (Deng et al, ; Zhou et al, ) and microcystins (Li et al, ) on the growth of phytoplankton in cyanobacterial bloom periods in Lake Taihu through field monitoring and laboratory experiments. However, the differences and dynamics of the physiological photosynthetic activity of the phytoplankton community during cyanobacterial bloom formation have been largely overlooked and still lack adequate research, especially in natural communities.…”
Section: Introductionmentioning
confidence: 99%
“…Although the response of the total biomass of the phytoplankton community to nutrient additions has been well studied in hypereutrophic areas of Lake Taihu, such as Meiliang Bay, the internal interaction between algal population biomass and photosynthetic performance remains unclear. Moreover, recent studies have demonstrated that extremely high nutrient levels may result in the dominance of green algae over cyanobacteria in Lake Taihu (Ma et al, ). However, little is known about the differences between cyanobacteria and green algae activities during the bloom period.…”
Section: Introductionmentioning
confidence: 99%